Stability of cylindrical shells with one plane of elastic symmetry under axial compression and torsion - Trach, V. M. (International applied mechanics, 2006)
A numerical technique is developed for stability analysis of laminated cylindrical shells with one plane of symmetry subject to axial compression and torsion. Shells filament-wound in directions other than the coordinate axes are considered as a special case. These shells are analyzed for stability under axial compression, external pressure, and torsion. It is shown that shells with a great number of plies and different ply angles may be considered orthotropic